T2-Signal of ulnar nerve branches at the wrist in guyon’s canal syndrome - Hayes, Jennifer; Bäumer, Philipp; Milford, David; Bendszus, Martin; Pham, Mirko (PLOS ONE, 2012)
Objective To evaluate T2-signal of high-resolution MRI in distal ulnar nerve branches at the wrist as diagnostic sign of guyon’s-canal-syndrome (GCS). Materials and Methods 11 GCS patients confirmed by clinical/electrophysiological findings, and 20 wrists from 11 asymptomatic volunteers were prospectively included to undergo the following protocol: axial T2-weighted-fat-suppressed and T1-weighted-turbo-spin-echo-sequences (3T-MR-scanner, Magnetom/Verio/Siemens). Patients were examined in prone position with the arm extended and wrist placed in an 8-channel surface-array-coil. Nerve T2-signal was evaluated as contrast-to-noise-ratios (CNR) from proximal-to-distal in ulnar nerve trunk, its superficial/sensory and deep/motor branch. Distal motor-nerve-conduction (distal-motor-latency (dml)) to first dorsal-interosseus (IOD I) and abductor digiti minimi muscles was correlated with T2-signal. Approval by the institutional review-board and written informed consent was given by all participants. Results In GCS, mean nerve T2-signal was strongly increased within the deep/motor branch (11.7±4.8 vs.controls:−5.3±2.4;p = 0.001) but clearly less and not significantly increased in ulnar nerve trunk (6.8±6.4vs.−7.4±2.5;p = 0.07) and superficial/sensory branch (−2.1±4.9vs.−9.7±2.9;p = 0.08). Median nerve T2-signal did not differ between patients and controls (−9.8±2.5vs.−6.7±4.2;p = 0.45). T2-signal of deep/motor branch correlated strongly with motor-conduction-velocity to IOD I in non-linear fashion (R2 = −0.8;p<0.001). ROC-analysis revealed increased nerve T2-signal of the deep/motor branch to be a sign of excellent diagnostic performance (area-under-the-curve 0.94, 95% CI: 0.85-1.00; specificity 90%, sensitivity 89.5%). Conclusions Nerve T2-signal increase of distal ulnar nerve branches and in particular of the deep/motor branch is highly accurate for the diagnostic determination of GCS. Furthermore, for the first time it was found in nerve entrapment injury that T2-signal strongly correlates with electrical-conduction-velocity.
Gesehen am 23.10.2018